A case report on Sarcoidosis - Deb, Sudip Ranjan; Sarkar, Ratul; Hasan, Pratyay; Mukerrama, Shegufta Mishket; Baral, Prianka; Kabir, Ahmedul; Hossain, Mahbub (Journal of Dhaka Medical College, 2015)
Sarcoidosis is a multisystem disease that may involve almost any organ system. Infiltration with non-caseating granulomas is the hallmark of the disease, and it may result in various clinical manifestations. Since the first description of the disease by British dermatologist Jonathan Hutchison in 1869, sarcoidosis has been seen in almost every part of the world and continues to engender considerable interest among clinicians because of its unknown aetiology, protean manifestations, and variable course and prognosis. Here we report a 65-year old woman who presented to us with a rather atypical presentation of sarcoidosis- subcutaneous nodules. Later, on subsequent diagnostic work-up, she was found to have bilateral hilar and mediastinal lymphadenopathy and pulmonary reticular lesions. It is a bit unusual to have only subcutaneous nodules as the presenting complaint of sarcoidosis without any prominent systemic and respiratory symptoms, which is what prompted this report. DOI: http://dx.doi.org/10.3329/jdmc.v22i2.21549 J Dhaka Medical College, Vol. 22, No.2, October, 2013, Page 225-228